2016
DOI: 10.1186/s40794-016-0022-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of active trachoma and associated risk factors among children in Gazegibela district of Wagehemra Zone, Amhara region, Ethiopia: community-based cross-sectional study

Abstract: BackgroundTrachoma continues to be hyperendemic in many rural areas of Ethiopia. The aim of this study was to determine the prevalence and associated risk factors of active trachoma among children in Gazegibela district, Ethiopia.MethodsA community-based cross-sectional study was conducted in April 2015 among children aged 1–9 years. Data were collected through an interview and eye examinations. Descriptive and logistic regression analyses were performed.ResultsAmong 601 children, 315 (52.4 %) were positive fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
17
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 5 publications
11
17
6
1
Order By: Relevance
“…On the other hand, the prevalence of active trachoma in this study was lower than a study report from prevalence Gazegibela district, Amhara region, which reported 52.4% [17], and a report from Dalocha district, central Ethiopia reported 51.5% prevalence [20]. This difference might be due to infrastructure and health service coverage difference, in addition to Gazegibela district, which is repeatedly drought affected and one of the food insecure districts of the Amhara region.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…On the other hand, the prevalence of active trachoma in this study was lower than a study report from prevalence Gazegibela district, Amhara region, which reported 52.4% [17], and a report from Dalocha district, central Ethiopia reported 51.5% prevalence [20]. This difference might be due to infrastructure and health service coverage difference, in addition to Gazegibela district, which is repeatedly drought affected and one of the food insecure districts of the Amhara region.…”
Section: Discussioncontrasting
confidence: 91%
“…Unlike the findings from the north and south Wollo Zones of Amhara region, this study finding a significant association between the source of water and the presence of active trachoma [16]. In line with this finding, a study from Gazegibela district (north Ethiopia) reported the source of water supply has been significantly associated with the occurrence of active trachoma among children [17].…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The prevalence of active trachoma (TF or TI) was 10.3% in this study, which was lower compared to other studies conducted in Ethiopia. [ 9 11 12 ]…”
Section: Discussionmentioning
confidence: 99%